2021
DOI: 10.3389/fimmu.2021.766757
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 Regulates Diametrically Opposed Biological Functions of Regulatory T Cells

Abstract: Regulatory T cells (Tregs) are considered important for controlling the onset and development of autoimmune disease. Although studies have shown that miR-21 is expressed at higher levels in Treg cells, it remains largely elusive whether miR-21 regulates the immune-suppressive function of Tregs. In the current study, we generated mice lacking miR-21 specifically in their Tregs and investigated the role of miR-21 in regulating Treg function both in vitro and in vivo. Our study revealed that Tregs lacking miR-21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…While some studies show that transfection of naïve human CD4 T cells with miR-21 is sufficient to induce Treg development by increasing Foxp3, TGFb, and IL-10, another study found that miR-21 promotes RORgt and suppresses Foxp3 and IL-10 (180, 186, 187). Indeed, Treg specific depletion of miR-21 in mice induced the expression of both IL-17 and IL-10 indicating that miR-21 may play a role in opposing pathways (184). In line with these opposing observations, increased miR-21 expression inhibited FOXP3+ Tregs in human gastric cancer (188) whereas it induced FOXP3 in human and mouse autoimmunity (182,183).…”
Section: Non-coding Rnas During Autoimmunitymentioning
confidence: 83%
See 1 more Smart Citation
“…While some studies show that transfection of naïve human CD4 T cells with miR-21 is sufficient to induce Treg development by increasing Foxp3, TGFb, and IL-10, another study found that miR-21 promotes RORgt and suppresses Foxp3 and IL-10 (180, 186, 187). Indeed, Treg specific depletion of miR-21 in mice induced the expression of both IL-17 and IL-10 indicating that miR-21 may play a role in opposing pathways (184). In line with these opposing observations, increased miR-21 expression inhibited FOXP3+ Tregs in human gastric cancer (188) whereas it induced FOXP3 in human and mouse autoimmunity (182,183).…”
Section: Non-coding Rnas During Autoimmunitymentioning
confidence: 83%
“…miR-21 acts indirectly to positively regulate Foxp3 expression (180); however, in autoimmunity, reduced miR-21 expression is correlated with increased STAT3 and reduced STAT5 and Foxp3 expression (26,(181)(182)(183). miR-21 directly targets STAT3 resulting in its downregulation and subsequently reduces effector molecules IL-17 and IL-22 (182,184). Maresin 1 (MaR1) and the EGF/c-Jun pathway have both been shown to induce miR-21, restore Treg : Teff ratios through FOXP3 induction, and reduce autoimmunity (183,185).…”
Section: Non-coding Rnas During Autoimmunitymentioning
confidence: 99%
“…Moreover, it could be associated with T cell differentiation, due to its interaction with STAT3. This inhibits the transformation of Tregs into the cells secreting IL-17 [102]. Similarly, another study demonstrated that Maresin1, a macrophage-derived mediator, suppressed Th17 and enhanced the Treg differentiation by miR-21 overexpression [103].…”
Section: Mesenchymal Stem-cell-derived Extracellular Vesicles and T C...mentioning
confidence: 92%